Defluoridation using biomimetically synthesized nano zirconium chitosan composite: kinetic and equilibrium studies - Prasad, Kumar Suranjit; Amin, Yesha; Selvaraj, Kaliaperumal (Journal of Hazardous Materials, 2014)
{The present study reports a novel approach for synthesis of Zr nanoparticles using aqueous extract of Aloe vera. Resulting nanoparticles were embedded into chitosan biopolymer and termed as CNZr composite. The composite was subjected to detailed adsorption studies for removal of fluoride from aqueous solution. The synthesized Zr nanoparticles showed UV-vis absorption peak at 420 nm. TEM result showed the formation of polydispersed, nanoparticles ranging from 18 nm to 42 nm. SAED and XRD analysis suggested an fcc (face centered cubic) Zr crystallites. EDAX analysis suggested that Zr was an integral component of synthesized nanoparticles. FT-IR study indicated that functional group like -NH
Keywords: Aloe vera; Chitosan; FT-IR spectroscopy; Sorption; Zirconium nanoparticles